A Study On Preventive Role Of Ayurveda In Lifestyle Disorders - Verma, Rakesh Kumar; Kumar, Manish (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is not only a medical science but also tells about the ways of living life. In Ayurveda, the most emphasis is given on avoiding diseases; it is given on living a healthy life. In today’s era, it has become more important to use the rules of Ayurveda because a person does not pay attention to his health, due to which the person has to face many health-related problems. Today the whole world is suffering from lifestyle disorders i.e., high blood pressure, Includes diabetes, heart disease, depression, etc. Till now no effective treatment of all these diseases is available with modern science, due to which we should avoid these diseases by following the rules of Ayurveda. In this article, we will get brief information about those Ayurveda rules from which these diseases can be avoided.